2020
DOI: 10.21203/rs.3.rs-57181/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteinuria in COVID-19: prevalence, characterization and prognostic role

Abstract: Background: Proteinuria has been commonly reported in patients with COVID-19, suggesting a renal involvement in this infection. However, only dipstick tests have been used thus far. Here, the quantification and characterization of proteinuria and hematuria are investigated. Their potential association with mortality was assessed. Methods: This retrospective, observational and monocentric study includes 153 patients hospitalized with COVID-19 between March 28th and April 30th 2020, in whom total proteinuria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…While mechanistic evaluation with kidney biopsies was not reported in our study, we feel that our data implicate a tubulointerstitial pattern of damage caused by the SARS-CoV2 virus, resulting in non-albumin proteinuria, trace glucosuria, and hematuria 20,27,28 . 25.5% of AKI-D patients had nephrotic-range proteinuria in our study, supporting what others have shown to be a range of kidney injury pathologies in COVID-19 including both tubular injury and glomerular processes [29][30][31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While mechanistic evaluation with kidney biopsies was not reported in our study, we feel that our data implicate a tubulointerstitial pattern of damage caused by the SARS-CoV2 virus, resulting in non-albumin proteinuria, trace glucosuria, and hematuria 20,27,28 . 25.5% of AKI-D patients had nephrotic-range proteinuria in our study, supporting what others have shown to be a range of kidney injury pathologies in COVID-19 including both tubular injury and glomerular processes [29][30][31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 54%
“…Notably, the incidence of proteinuria and hematuria may actually exceed that of AKI, raising the possibility that urinary abnormalities could serve as an earlier or more sensitive marker of disease 16 . Others have demonstrated an association of proteinuria and hematuria with mortality in the setting of COVID-19 4,[17][18][19][20][21][22][23][24][25] . However, to our knowledge, there has been only one other publication evaluating the association of proteinuria with the need for dialysis in 84 patients with formal urine protein/creatinine ratios 26 .…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a novel nosological entity, with a broad clinical spectrum. The early description of the entity logically focused on lung involvement, although an increasing number of reports have progressively highlighted the impact of the SARS-CoV-2 on other organs including the kidneys 3,[6][7][8] . Furthermore, correlations between extra-respiratory viral tropism, disease severity, and increased risk of premature death within the first 3 weeks of disease have been highlighted 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The earliest report showed that proteinuria and hematuria were detected at hospital admission in 43.9% and 26.7% of patients with COVID-19, while ~15% of them presented with elevated levels of serum creatinine and/or blood urea nitrogen 5 . Proteinuria characterization suggests a tubular origin 8 . Acute kidney injury (AKI) has been identified as an independent risk factor for in-hospital mortality [3][4][5]9 .…”
Section: Introductionmentioning
confidence: 99%
“…Proteinuria might result from a proximal tubular dysfunction. COVID-19-induced AKI and proteinuria have been associated with poor short-term outcomes in hospitalized patients [2,3]. However, the middle-and long-term consequences of SARS-CoV-2 infection on kidney function remain unknown.…”
mentioning
confidence: 99%